Effect of Sulfur and Boron on Nutrients in Mungbean (Vigana radiata L.) and Soil Health - Shamsuddoha, A. T. M.; Anisuzzaman, M.; Sutradhar, G. N. C.; Hakim, M. A.; Bhuiyan, M. S. I. (International Journal of Bio-resource and Stress Management, 2011)
A field experiment was conducted at the research farm of Sher-e-Bangla Agricultural University, Dhaka, Bangladesh during the period from February to May 2008 to study the effects of sulfur and boron on nutrients of mungbean and the soil health. The variety BARI mung-6 was used as the test crop. In most of the cases of sulfur and boron application, the individual treatments 8 kg S and 2 kg B ha-1 showed the highest nutrient concentration and maximum uptake of N, P, K, S and B by the seed and the stover of mungbean. Side by side sulfur and boron with the 8 kg S plus 2 kg B ha-1 treatment combination revealed the highest nutrient concentration and maximum uptake of N, P, K, S and B by the seed and the stover of mungbean. In case of S treatments the highest pH, organic matter, total N, available P, exchangeable K, available S and available B was recorded from S8 ( 8 kg S ha-1 ) and the lowest pH, organic matter, total N, available P, exchangeable K, available S and available B was observed from S0 (no sulfur) treatment. In case of B application the highest pH, organic matter, total N, available P, exchangeable K, available S and available B was recorded from B2 (2 kg B ha-1) and the lowest pH, organic matter, total N, available P, exchangeable K, available S and available B was found from B0 (no boron) treatment. For combined application of S and B the highest pH, organic matter, total N, available P, exchangeable K, available S and available B was recorded from S8B2 (8 kg S ha-1 and 2 kg B ha-1) treatment combination causing better soil health and the lowest pH, organic matter, total N, available P, exchangeable K, available S and available B was observed from S0B0 (no sulfur and boron). Individually 8 kg S and 2 kg B ha-1, but as combined 8 kg S plus 2 kg B ha-1 treatments revealed the highest nutrient concentration and maximum uptake of N, P, K, S and B by the seed and the stover of mungbean and also showed the improvement in the nutrient status of post harvest soil.